Correlation of Low CD73 Expression on Synovial Lymphocytes With Reduced Adenosine Generation and Higher Disease Severity in Juvenile Idiopathic Arthritis. Issue 2 (February 2015) - Botta Gordon‐Smith, Sophie; Ursu, Simona; Eaton, Simon; Moncrieffe, Halima; Wedderburn, Lucy R.
<x xml:space="preserve">Abstract</x> Objective To investigate the expression and adenosine‐generating activity of the ecto‐5′‐nucleotidase CD73 on synovial fluid mononuclear cells (SFMCs) and peripheral blood mononuclear cells (PBMCs) from children with juvenile idiopathic arthritis (JIA). Methods Given the role of CD73 protein in the production of antiinflammatory adenosine and its intersection with inflammatory biologic pathways, the expression of CD73 on SF and PB lymphocytes from patients with JIA and PB lymphocytes from healthy control subjects was determined by flow cytometry. The AMPase activity of CD73 on PBMCs and SFMCs was measured by high‐performance liquid chromatography. The effects of cell activation on CD73 expression were examined by in vitro culture of PBMCs. Results CD8+ and CD19+ SFMCs from patients with JIA expressed decreased levels of CD73 when compared to paired PBMCs from JIA patients and PBMCs from healthy controls. When the percentages of CD73+ synovial lymphocytes were compared between the 2 clinical forms of oligoarthritis, children with extended oligoarthritis showed lower CD73 expression compared to those with the milder form of the disease. CD8+ SFMCs had a lower ability to produce adenosine from etheno‐AMP compared to CD8+ PBMCs. T cell activation through the T cell receptor (TLR) of CD8+CD73+ cells and B cell activation through TLR‐9 resulted in reduced expression of CD73. This down‐regulation occurred on dividing cells. Conclusion These findings show that low CD73 expression on T and B cells in the inflamed site is related to cell proliferation and is correlated with the clinical severity of oligoarticular JIA. The decreased CD73 expression on SFMCs, in turn, results in reduced adenosine production, which leads to a decreased potential for antiinflammatory activity.